2007
DOI: 10.1007/s00122-007-0617-y
|View full text |Cite
|
Sign up to set email alerts
|

Identification, validation and survey of a single nucleotide polymorphism (SNP) associated with pungency in Capsicum spp.

Abstract: A single nucleotide polymorphism (SNP) associated with pungency was detected within an expressed sequence tag (EST) of 307 bp. This fragment was identified after expression analysis of the EST clone SB2-66 in placenta tissue of Capsicum fruits. Sequence alignments corresponding to this new fragment allowed us to identify an SNP between pungent and non-pungent accessions. Two methods were chosen for the development of the SNP marker linked to pungency: tetra-primer amplification refractory mutation system-PCR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 40 publications
1
25
0
2
Order By: Relevance
“…Dentre as características de importância econômica, a pungência é o principal atrativo deste gênero, sendo conferida por substâncias alcalóides denominadas capsaicinóides. Esses alcalóides têm sido amplamente estudados (Henry & Emery, 1986;Caterina, 2000;Blum et al, 2002;Daood et al, 2002) sendo sintetizados no tecido da placenta e armazenados em células epidérmicas (Garcés-Claver et al, 2007;Stewart et al, 2007).…”
Section: Pesquisa / Researchunclassified
See 1 more Smart Citation
“…Dentre as características de importância econômica, a pungência é o principal atrativo deste gênero, sendo conferida por substâncias alcalóides denominadas capsaicinóides. Esses alcalóides têm sido amplamente estudados (Henry & Emery, 1986;Caterina, 2000;Blum et al, 2002;Daood et al, 2002) sendo sintetizados no tecido da placenta e armazenados em células epidérmicas (Garcés-Claver et al, 2007;Stewart et al, 2007).…”
Section: Pesquisa / Researchunclassified
“…Nestes casos uma alternativa para avaliação da pungência é o uso de marcadores moleculares, onde a análise pode ser realizada em estágios iniciais de desenvolvimento da plântula, utilizando apenas folhas jovens e, com isso, reduzindo o tempo para verificação dos genótipos (Garcés-Claver et al, 2007). A determinação de pungência através de marcadores moleculares foi realizada a partir do loco Pun1 (Stellari et al, 2010;Wyatt et al, 2012), principal gene responsável pela biossíntese de capsaicinoides, sendo o único loco conhecido, até o momento, com efeito quantitativo sobre o acúmulo de pungência (Blum et al, 2003;Lang et al, 2006;Stellari et al, 2010).…”
Section: Q U I D E C H R O M a T O G R A P H Y H P L C )unclassified
“…Garce's-Claver and collaborators [24] reported that the smaller fragment of the inner primers is disadvantaged by the formation of larger fragments, resulting in a weaker intensity of the band. In our case, with the same concentrations of inner primers, not only the intensities of the allelic bands were different (the A allele showed higher intensity respect to the G allele) but also the amplification of both alleles was observed in the homozygous G/G by ARMS modified PCR (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…For the plant biotech industry, it represents a useful tool for the determination of copy numbers [13][14], transgenic plants [15], and single nucleotide polymorphisms (SNPs) [16,17]. SNPs are rare, single nucleotide substitutions, and small insertion/deletion (InDel) mutations have been widely used in a variety of research areas, such as molecular markers [18], biodiversity assessment [19], and high-density genome-wide scans [20]. As a powerful tool in plant breeding, the SNP analysis technique, which can analyze any change in nucleotide sequence, allows the identification of the genotype of each plant.…”
Section: Introductionmentioning
confidence: 99%